The Capsaicin Paradox: Pain Relief by an Algesic Agent - Jancso, Gabor; Oszlacs, Orsolya; Santha, Peter (Anti-Inflammatory & Anti-Allergy Agents in Medicinal Chemistry, 2011)
Chemosensitive primary sensory neurones expressing the TRPV1 receptor, a molecular integrator of diverse noxious stimuli, play a fundamental role in the sensation of pain. Capsaicin, the archetypical ligand of the TRPV1 receptor, is one of the most painful chemical irritants, and its acute administration onto the skin and mucous membranes elicits severe pain. However, repeated or high-dose applications of capsaicin, and/or its administration through specific routes dramatically decreases the sensitivity of the innervated tissues to noxious chemical and heat stimuli. This review surveys the mechanisms of the antinociceptive, anti-inflammatory and anti-hyperalgesic effects of vanilloid agonists applied topically, or perineurally, or injected into the subarachnoid space in animal experiments and to put these data into a clinical perspective. The great body of available experimental evidence indicates that vanilloid agonists exert their antinociceptive actions through TRPV1 receptor-mediated selective neurotoxic/neurodegenerative effects directed against somatic and visceral C-fibre nociceptive primary afferent fibres. It is expected that vanilloid agonists will broaden the palette of analgesic drugs which do not cause addiction and tachyphylaxis.
Keywords: Analgesia